STUDI KUANTITATIF PEMANFAATAN BPJS KESEHATAN: APAKAH ASPEK DEMOGRAFI BERPENGARUH? - Nur Hayati; Ayu Dewi Mayasari; Rahmawati Rahmawati; Ryryn Suryaman Prana Putra (Ensiklopedia Research and Community Service Review, 2026)
Based on document searches, Deli Serdang Regency still faces challenges in expanding JKN coverage, especially among unregistered communities. BPJS Kesehatan coverage is still inadequate, and there are limitations in the information they obtain regarding service procedures, administrative requirements, and the types of health services covered by BPJS Kesehatan. The purpose of this study is to determine the relationship between demographic aspects and the utilization of BPJS Kesehatan. The research design used in this study was cross-sectional. The research was conducted at the Tuntungan Community Health Center in September 2025. The research population consisted of all BPJS Kesehatan users in the Tuntungan Community Health Center working area. The sample consisted of 80 respondents. The sampling technique used was simple random sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between age (p value: 0.032) and education (p value: 0.040). It is recommended that health center staff improve health services to increase the utilization of BPJS Kesehatan services.